Implementasi Kurikulum dan Evaluasi Pada SMA Negeri 18 Jakarta - Muhammad Amin; Wahyudin Wahyudin; Hanafiah Hanafiah (Peneliti.net, 2023)
The purpose of this study was to determine the implementation of curriculum management at SMA Negeri 18 Jakarta in terms of planning, implementation and obstacles. This research uses a descriptive method with a qualitative approach. Data collection techniques were carried out through interviews, observation, and documentation. The subjects of this study were: school principals, vice principals for curriculum, and teachers. The results of the study show: (1) curriculum planning starts with syllabus development by designing lessons that contain teaching material plans, material grouping, and material presentation. This can be seen from the annual program, semester program, lesson plans, minimum completeness criteria; (2) Implementation of the curriculum carried out by the teacher to carry out learning which includes teacher assignments, giving additional assignments, preparing schedules, dividing study groups, filling in teacher and student absences, determining extra-curricular activities, carrying out exams and filling in report cards and remedial as well as the teacher's role in implementing the curriculum as well as making decisions and implementing teaching programs; (3) There are significant evaluations/obstacles experienced by the principal in implementing the curriculum at SMA Negeri 18 Jakarta. However, guidance from the principal and teacher commitment is needed to implement the curriculum at SMA Negeri 18 Jakarta. Guidance from school principals with rewards and punishments, so that teachers who are committed get rewards and vice versa